Evaluasi Sistem Informasi Distribusi Es Kristal Berbasis Web Menggunakan System Usability Scale (SUS) dan User Acceptance Testing (UAT) - Rena Judha Wijayanti; Sri Dianing Asri (JSAI (Journal Scientific and Applied Informatics), 2026)
This study aims to evaluate the usability and user acceptance of a web-based crystal ice distribution information system developed to support the operations of PT Eshokita Tubindo Mandiri. The system was developed using the Waterfall method with stages of requirements analysis, design, implementation, and testing. The system evaluation was conducted using the System Usability Scale (SUS) and User Acceptance Testing (UAT) on 13 respondents who were directly involved in the distribution process. The test results showed a SUS score of 82.11, which is classified as very good, and all system functions were accepted by users based on the UAT results. However, the scope of testing was still limited to one company and a relatively small number of respondents. This study contributes to the evaluation of cold chain distribution information systems based on usability and user acceptance.